Strong Interlayer Transition in Few‐Layer InSe/PdSe2 van der Waals Heterostructure for Near‐Infrared Photodetection. (4th August 2021) - Ahmad, Waqas; Liu, Jidong; Jiang, Jizhou; Hao, Qiaoyan; Wu, Di; Ke, Yuxuan; Gan, Haibo; Laxmi, Vijay; Ouyang, Zhengbiao; Ouyang, Fangping; Wang, Zhuo; Liu, Fei; et al.
Abstract: Near infrared (NIR) photodetectors based on 2D materials are widely studied for their potential application in next generation sensing, thermal imaging, and optical communication. Construction of van der Waals (vdWs) heterostructure provides a tremendous degree of freedom to combine and extend the features of 2D materials, opening up new functionalities on photonic and optoelectronic devices. Herein, a type‐II InSe/PdSe2 vdWs heterostructure with strong interlayer transition for NIR photodetection is demonstrated. Strong interlayer transition between InSe and PdSe2 is predicted via density functional theory calculation and confirmed by photoluminance spectroscopy and Kelvin probe force microscopy. The heterostructure exhibits highly sensitive photodetection in NIR region up to 1650 nm. The photoresponsivity, detectivity, and external quantum efficiency at this wavelength respectively reaches up to 58.8 A W −1, 1 × 10 10 Jones, and 4660%. The results suggest that the construction of vdWs heterostructure with strong interlayer transition is a promising strategy for infrared photodetection, and this work paves the way to developing high‐performance optoelectronic devices based on 2D vdWs heterostructures. Abstract : Strong interlayer transition in few layers of InSe/PdSe2 heterojunction is presented. Interlayer transition at the interface is certified both theoretically (density functional theory) and experimentally (photoluminance spectroscopy and Kelvin probe force microscopy). Owing to the strong interlayer transition, the heterojunction shows a wide spectrum response (532 to 1650 nm) with ultra‐high photoresponsivity 58.8 A W −1 at 1650 nm.